Evaluation of Polyethylene Wax and Paraffin as Anti Wear and Extreme Pressure Additives in Virgin Sesame Base Stock - Delgado Tobón, Arnoldo Emilio; Aperador Chaparro, William Arnulfo (TECCIENCIA, 2020)
This research was carried out in order to study the performance of polyethylene wax and paraffin as additives to improve the lubricating characteristics of virgin sesame oil. Three blends of sesame oil were prepared as follows: without additive (control), polyethylene wax (1%w/w) and paraffin (1%w/w). The lubricating properties of the blends were characterized by tribology four balls: the average diameter of wear scare and the coefficient of friction were determined from the Wear Preventive test; the last non-seizure load and the weld point were calculated by the Extreme Pressure test. The morphology of the ball-scares from the Wear Preventive test were observed through Electronic Scanning Microscopy. The ball scares from the Extreme Pressure test were observed by optical microscopy. The polyethylene wax and paraffin at concentrations of 1% w/w did not show a significant improvement in the lubricant characteristics of virgin sesame oil, according to the results obtained from the tribology testing.